Leveraging Artificial Intelligence to Enhance Physical Education in Elementary Schools: A Systematic Review and Future Directions - Pratiwi, Febriana; Sheila Dwi Loviani (Indonesian Journal of Sport Management, 2024)
Although artificial intelligence (AI) is transforming many aspects of education, its application in physical education is a relatively new but promising field. Some of the key points explored in this review include the overall benefits of AI in elementary school physical education learning, specific applications, challenges to consider, ethical implementation of AI use in physical education such as data privacy issues, and current research directions. This systematic review will focus on the potential of AI to enhance the physical education experience for elementary school children. Following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA), 18 studies related to AI in physical education were included in the final synthesis. The application of artificial intelligence in physical education is gradually influencing the improvement of teaching and learning activities in physical education classes. Artificial intelligence in physical education offers great potential to provide personalized instruction, real-time feedback and assessment, and a diverse learning environment.  The findings of this study indicate that many studies have explored the use of AI to enhance physical education classes. However, studies reviewing and analyzing the use of artificial intelligence in physical education learning at the elementary school level are scarce.